The rise and fall of a dot-com pioneer in a developing country - Effah, J. (My University, 2014)
Purpose ‐ The purpose of this paper is to investigate the experiences of dot-com pioneers in developing countries to complement the experience of their counterparts from the developed world as documented in the dot-com boom and bust literature. Beginning from this literature, dot-com phenomenon in the developed world has attracted much research. However, despite some entrepreneurial attempts to promote the innovation in the developing world, less is known about dot-coms there. Design/methodology/approach ‐ The study follows interpretive case study methodology and actor-network theory to understand the formation, initial success and final failure of a dot-com pioneer in the developing country of Ghana. Findings ‐ The developing country dot-com pioneer transferred e-tail technology from the developed world. The under-developed infrastructure in the developing world forced the technology to be adapted to local context. The firm managed to succeed temporarily by engaging with actors from both the developed and the developing world. It, however, collapsed largely due to inflation in its developing country context, which rendered its stockless business model with purchasing on order to deliver economically unfeasible as purchasing prices outrun sales prices. Research limitations/implications ‐ The findings are based on historical reconstruction of events which may differ from current circumstances. The study, however, demonstrates how pioneer dot-coms in developing countries may have fared and offers implications for research and practice. Practical implications ‐ Stockless e-business model with purchase on order to supply may not be economically feasible under inflationary conditions as purchase prices may outstrip sales prices. Entrepreneurs need to pay attention not only to the virtual world but also the physical world which equally contribute to e-business practice. Originality/value ‐ The paper is the first attempt to offer insight into the experiences of developing country dot-com pioneers to complement the literature from the developed world. The rise and fall of a dot-com pioneer in a developing country. Available from: http://www.researchgate.net/publication/263555989_The_rise_and_fall_of_a_dot-com_pioneer_in_a_developing_country [accessed Jul 22, 2015].